Insolvenzrechtliche Gläubigerautonomie im Gläubigerausschuss - Thoma, Carl-Friedrich (Abhandlungen zum Deutschen und Europäischen Gesellschafts- und Kapitalmarktrecht (AGK), 2019)
»Creditors' Autonomy in German Creditors' Committees« Creditors' Autonomy is regarded as a principle of German insolvency law. This thesis questions the meaning and efficiency of this term and ultimately supports the efforts to achieve a stronger preventive restructuring framework and crisis management beyond Creditors' Autonomy. At the same time, the thesis treats the creditors' committee as a highly specialised and efficient organ of insolvency proceedings. It is examined for its economic significance, its legal structure and its development potential as an instrument of Creditors' Autonomy where preventive measures have failed.